Tipos de liderança do enfermeiro de centro cirúrgico - Maia, Silene Costa (1993)
This study has the objective to identify the kind of leadership of the Nurse in the Surgical Center at the hospitais of João Pessoa in Paraíba state/Brazil. The data was collected from interviews throveh applications. The study revealed that those nurses have a certain kind of leadership, predominantly the democratic.